The spontaneous fulfillment of desire : harnessing the infinite power of coincidence - Chopra, Deepak (Three Rivers Press, 2003)
Explains how to access the everyday coincidences of life and how to understand and reconnect with the underlying field of infinite possibilities in order to fulfill one's deepest desires and transform one's life.